Biological diversity and community structure of the lchthyofauna on vessel reefs in the Coast of Recife (PE) - Brazil - Coxey, Mariana Sofia Gameiro Silva (2015)
Dissertação de mestrado, Biologia Marinha (Ecologia e Conservação Marinha), Faculdade de Ciências do Mar e do Ambiente, Universidade do Algarve, 2008